1999
DOI: 10.1523/jneurosci.19-22-09848.1999
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Channels Formed by the Neuronal Gap Junction Protein Connexin36

Abstract: The expression and functional properties of connexin36 (Cx36) were examined in two communication-deficient cell lines (N2A-neuroblastoma and PC-12 cells) transfected with Cx36 and in hippocampal neurons that express the connexin endogenously. Transfected cells expressed the expected 2.9 kb Cx36 transcript and Cx36 immunoreactivity, whereas nontransfected cells were devoid of Cx36. The relationship between steadystate junctional conductance ( g j ) and transjunctional voltage was well described by a two-state B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
205
2
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 259 publications
(241 citation statements)
references
References 30 publications
30
205
2
4
Order By: Relevance
“…Cx36 gap junction channels display very low voltage-sensitivity and a low single-channel conductance (~15 pS; Srinivas et al, 1999;Teubner et al, 2000). As far as we know, Cx36 KO mice have not been examined for electrical coupling with dual whole-cell recording of neighboring AII amacrine cells.…”
Section: Connexins Involved In Gap Junctions Of Aii Amacrine Cellsmentioning
confidence: 99%
“…Cx36 gap junction channels display very low voltage-sensitivity and a low single-channel conductance (~15 pS; Srinivas et al, 1999;Teubner et al, 2000). As far as we know, Cx36 KO mice have not been examined for electrical coupling with dual whole-cell recording of neighboring AII amacrine cells.…”
Section: Connexins Involved In Gap Junctions Of Aii Amacrine Cellsmentioning
confidence: 99%
“…However, we should remember that A-type HCs have exceptional dye coupling properties. They are coupled via Cx50 gap junctions which have a much higher unitary conductance (220pS) (Srinivas et al, 1999a) compared to 15pS for Cx36 (Srinivas et al, 1999b). Furthermore, A-type HCs are coupled, at least in part, via giant plaques which may occupy 50 μm 2 and contain hundreds of thousands of gap junctions channels (O'Brien et al, 2006).…”
Section: Meclofenamic Acid Is a Potent Water-soluble Reversible Gapmentioning
confidence: 99%
“…First, they imply that neither Cx36 nor pannexin1 are per se sufficient to form functional "hemichannels" in insulin-producing cells. Cx36 makes β-to-β-cell channels that are permeated by a variety of tracers, including ethidium bromide (Ravier et al 2005;Charpantier et al 2007), and features one of the smallest unitary conductances (10 to 15 pS) yet observed between paired connexons (Srinivas et al 1999). Even considering that Cx36 conductance would be expected to increase by about twofold in single, unpaired connexons (Harris 2001;Verselis 2004, Spray et al 2006), it is conceivable that Cx36 "hemichannels" may not provide a sufficient permeability to allow for a sizable passage of hydrophilic molecules across single cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…To validate our experimental approach, we used murine neuroblastoma cells of the N2A line, which have been reported to not express connexins (Srinivas et al 1999). These cells were first compared to the murine insulin-producing cells of the MIN6 line for connexin and pannexin expression, as assessed by reverse transcriptase-polymerase chain reaction (RT-PCR).…”
Section: N2a and Min6 Cells Differ In Connexin But Not Pannexin Exprementioning
confidence: 99%